(untitled) (Economics and region, 2024)
The purpose of the article is to substantiate a methodological approach to assessing the potential for secondary resource utilization of solid household waste in territorial communities. Effective solid waste management plays a key role in preserving the environment and ensuring the health of residents. The use of innovative technologies will allow for the maximum use of the potential of solid waste to create a sustainable and environmentally friendly society. In our opinion, increasing the volume of solid waste involved in recovery can contribute to improving the quality of the environment and improving the economic performance of business entities and territorial systems in general. However, to implement the solid waste management process, it is necessary to determine whether the necessary conditions exist for the effective use of the existing potential in this area – economic, technological, production, environmental and others, or whether they should be specified taking into account the tasks set for management entities. In general, the potential for secondary use of solid household waste is developing based on the resource balance of territorial communities and the efficiency of its functioning. The potential for secondary resource utilization of solid household waste is considered as a set of available resources necessary for the removal or recovery of solid household waste, and the existing system of infrastructure support for these processes. Effective implementation of the potential for secondary resource utilization of solid household waste is largely determined by the balance of available resources and assumes the sustainability of infrastructure, which should be assessed and adjusted in accordance with the waste management program of the studied territorial communities. The article proposes criteria for the potential for secondary resource utilization of solid household waste in territorial communities. An algorithm for assessing the attractiveness of territorial communities for secondary resource utilization of solid household waste has been developed. A methodological approach to assessing the potential for secondary resource utilization of solid household waste in territorial communities is proposed, which involves taking into account, in addition to the resource component of the potential, the infrastructure component, which allows for the full development of waste for useful purposes. Based on the results of the calculation of the integral index of the potential level of secondary resource use of solid household waste of territorial communities, according to the proposed methodical approach, it is possible to evaluate the object according to the proposed classification.